Fluorescent Chitosan Modified with Heterocyclic Aromatic Dyes - Halina Kaczmarek (MDPI AG, 2021)
Chitosan is a valuable, functional, and biodegradable polysaccharide that can be modified to expand its applications. This work aimed to obtain chitosan derivatives with fluorescent properties. Three heterocyclic aromatic dyes (based on benzimidazole, benzoxazole, and benzothiazole) were synthesized and used for the chemical modification of chitosan. Emission spectroscopy revealed the strong fluorescent properties of the obtained chitosan derivatives even at a low N-substitution degree of the dye. The effect of high-energy ultraviolet radiation (UV–C) on modified chitosan samples was studied in solution with UV–Vis spectroscopy and in the solid state with FTIR spectroscopy. Moreover, cytotoxicity towards three different cell types was evaluated to estimate the possibilities of biomedical applications of such fluorescent chitosan-based materials. It was found that the three new derivatives of chitosan were characterized by good resistance to UV–C, which suggests the possibility of using these materials in medicine and various industrial sectors.